Curcumin, A Polyphenolic Curcuminoid With Its Protective Effects and Molecular Mechanisms in Diabetes and Diabetic Cardiomyopathy - Zheng, Jia; Cheng, Jing; Zheng, Sheng; Feng, Qianyun; Xiao, Xinhua (Frontiers in Pharmacology, 2018)
As the leading cause of morbidity and mortality in patients with diabetes, diabetic cardiomyopathy (DCM) imposes enormous burden on individuals and public health. Therapeutic regimes for DCM treatment have proven to be challenging, with limited efficacy, low compliance, and potential adverse effects. Curcumin, as the most active compound derived from the root of turmeric, exhibits strong anti-inflammation, antioxidant, and anti-apoptosis properties. Recently, clinical trials and preclinical studies have shown that curcumin exerts protective effects against a variety of diseases, including diabetes and its cardiovascular complications. In this review, the clinical trials about curcumin supplementation on diabetes and DCM are presented, and the specific mechanisms by which curcumin might mitigate diabetes and DCM are fully discussed. A better understanding of the pharmacological role of curcumin on diabetes and DCM can provide clinical implications for the intervention of the onset and development of diabetes and DCM.